2016
DOI: 10.1016/j.jjcc.2015.09.016
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of case-control studies of the association of migraine and patent foramen ovale

Abstract: PFO is associated with 3.4-fold migraine-with-aura and 2.5-fold migraine-with/without-aura prevalence but unassociated with migraine-without-aura prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 39 publications
4
57
0
Order By: Relevance
“…In a recent meta-analysis, PFO is associated with 2.5-fold increased prevalence for migraine and 3.4-fold increased prevalence migraine with aura [5]. In a cross sectional study, we have found increased prevalence of right-to-left shunts (RLs) (62.9% vs. 44.0%) and PFO (54.8% vs. 30.0%) in patients with migraine with aura (MA) compared with those with migraine without aura (MWOA) in Asian populations [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta-analysis, PFO is associated with 2.5-fold increased prevalence for migraine and 3.4-fold increased prevalence migraine with aura [5]. In a cross sectional study, we have found increased prevalence of right-to-left shunts (RLs) (62.9% vs. 44.0%) and PFO (54.8% vs. 30.0%) in patients with migraine with aura (MA) compared with those with migraine without aura (MWOA) in Asian populations [6].…”
Section: Introductionmentioning
confidence: 99%
“…There may exist a common pathophysiology of increased ischemic stroke risk in young stroke population and older adults with late onset of MA as shown in our study, suggestive of underlying triggers such as microemboli responsible for MA symptoms. Additionally, our results are consistent with previous epidemiological studies, that MO is not a significant risk factor for ischemic stroke, when excluding stroke related to cervical artery dissection …”
Section: Discussionmentioning
confidence: 95%
“…A recent meta-analysis of 21 randomized controlled trials confirmed that PFO is associated with 3.4-fold migraine with aura but that there is no association with migraine without aura [10]. Different pathophysiological mechanisms have been postulated like right-to-left shunting of small subclinical emboli and metabolites bypassing the pulmonary system and causing irritation of the trigeminal nerve or an increased platelet activation and aggregation in response to serotonin could possibly trigger migraine and aura (normally serotonin is metabolized in the pulmonary circulation by the lung monoamine oxidase) [11,12].…”
Section: Discussionmentioning
confidence: 99%